The Sustainable University of the Future Reimagining Higher Education and Research - Al-Maadeed, Mariam Ali S A.; Bouras, Abdelaziz; Al-Salem, Mohammed; Younan, Nathalie (Cham : Springer International Publishing : Imprint: Springer, 2023)
The Sustainable University of the Future discusses the rapid changes taking place within institutions of higher education-changes that have pushed universities to reconsider their traditional policies and plans. The book, which has its origins in the Qatar University Annual Research Forum and Exhibition (QUARFE) event "University of the Future" examines the many ways universities are trying to keep pace with this transformation, despite regional and international challenges. The book looks at the role of universities in meeting the United Nation's Sustainable Development Goals (SDGs), the impact of Industry 4.0, the social aspects of University 4.0, and the future of research-based universities. The need to adopt modern programs and tools is stressed, and ways to anticipate and plan for future challenges are explored. Explores the complex nature of higher education transformation; Examines the role of higher education transformation in sustainable development; Presents lessons learned from leading education experts. .
Does the University Have a Future? -- Humanizing Higher Education: University of the Future -- Role of Universities in Transforming Society: Challenges and Practices -- Sustainable Development Goals (SDGs) and University Transformation -- How to Include SDGs in the Teaching Curricula -- Social Innovation in Advancing SDGs -- Gender-Related and Women Empowerment Challenges -- Knowledge-Based, Innovation, and Entrepreneurial Driven Research and Teaching -- Towards Sustainable Smart Campuses: From AI-Based Platforms for Distance Learning to Virtual Teaching -- Impact of the Industry 4.0 on the University and on Cooperative Education -- Preparing Students for Industry 4.0 -- University 4.0: Social Aspects.
Keywords: Sustainability; Technical education; Education, Higher; Education and state; Sustainability; Engineering and Technology Education; Higher Education; Educational Policy and Politics